(untitled) (Journal of Medicine, 2012)
A rare and potentially life-threatening condition is reported. A young diabetic lady presented with septic shock and features of paralytic ileus. A plain abdominal radiograph suggested “megacolon with gas-fluid levels”. But high degree of clinical suspicion persuaded us to perform a CT scan of abdomen, which revealed emphysematous pyelonephritis. This enabled us to start early effective treatment and eventually save the patient. DOI: http://dx.doi.org/10.3329/jom.v13i1.10055 JOM 2012; 13(1): 72-74